E-224 Bilateral external carotid artery sacrifice in massive refractory hemorrhage of the pharynx: a case report. (23rd July 2022) - Esmaeil, S; Eltatawy, A; Hossein Abbasi, M; Mowla, A; Grossman, A; Prestigiacomo, C; Shirani, P
Abstract : Endovascular intervention can help clinicians in the control of extensive bleeding in vascular malformations, traumatic events, and during challenging intra-operative situations. Recently, unilateral embolization of the external carotid artery (ECA) or its branches in case of malignancy associated vessel blow-out (this was used in the past by several interventionists) was introduced as a valuable alternative to exploratory surgical interventions with favorable results. To date, therapeutic ligation of bilateral ECA has been reported once in the setting of intractable post-traumatic hemorrhage. However, the clinical outcome and safety of bilateral ECA ligation is unclear. We report a case of severe pharyngeal hemorrhage due to erosion from a previous laryngeal squamous cell carcinoma (SCC) who ultimately required permanent bilateral ECA sacrifice with no ischemic complications. This report suggests that bilateral ECA embolization may be safe in acute settings. In this report, the bleeding did not respond to conservative or surgical management and ECA embolization was used as a life-saving procedure in order to stop massive bleeding. Bilateral external carotid artery embolization is rarely employed because of the high risk of facial necrosis. Additionally, ECAs are also assumed to serve as potential blood reservoirs, particularly in the case of ICA occlusion where the ipsilateral ECA can significantly contribute to intracranial blood flow via collaterals. However, in this report, no complications were observed after the bilateral ECA was sacrificed. The possible explanation of bilateral ECAs occluding without causing tissue necrosis may be due to the presence of collaterals from the ipsilateral ICA territory, which was visualized on the control angiogram after left ECA embolization. In this report, embolization of the right ECA was performed after a minor extravasation in the initial DSA was detected. It has been documented that vascular abnormalities such as false aneurysms, arteriovenous shunts, or highly vascularized tumors can provide fast and accurate indication to target the bleeding site. It is further suggested that leakage flow is better visualized when the patient is actively bleeding during angiography and can help in targeting an active focus. Few reports have indicated bilateral ECA embolization as a life-saving technique in minimizing blood loss in cases of head trauma, surgery or tumor. However, in these studies the right and left ECAs were temporarily sacrificed or rather, embolization of each ECA was performed much later, and not as an immediate procedure thus depriving the opportunity for collateralization to develop. Abraham et.al, in their study, has performed bilateral external carotid artery (ECA)ligations in patients with ischemia due to 'stroke' and results indicated a consistent increase in blood flow to the internal carotid artery. Hence, in cases of extensive head and neck bleeding, permanent, bilateral ECA sacrifice can be considered as a therapeutic option and a potentially life-saving procedure. Disclosures: S. Esmaeil: None. A. Eltatawy: None. M. Hossein Abbasi: None. A. Mowla: None. A. Grossman: None. C. Prestigiacomo: None. P. Shirani: None.